Desempeño profesional del docente en la modificación de conductas disruptivas en niños de educación general básica del subnivel elemental 3ero y 4to de una escuela fiscal del cantón Milagro de la provincia del Guayas - Carrera Salinas, Karla (2017)
Insufficiency in the handling of disruptive behaviors from the professional performance of the teacher is an unusual field of approach, since modifying disruptive behaviors is conceived for the teachers of Basic Education as a problematic which they have to address and give Solution a psychologist, however from the perspective of the author, the modification of disruptive behaviors must be approached from the teacher action within the classroom. Based on this, the current situation of teaching performance in three dimensions is diagnosed: attitude, approach and effectiveness of the approach to disruptive behaviors in the elementary students in the third and fourth year of basic education………..